The biology of lakes and ponds - Brönmark, Christer (Biology of habitats., 2005)
"This introduction to the biology of standing waters integrates the effects of abiotic constraints and biotic interactions at both the population and community level, and examines how the distribution and success of different organisms in this freshwater habitat can be explained and predicted"--Provided by publisher